Author Correction: The influence of latitude, geographic distance, and habitat discontinuities on genetic variation in a high latitude montane species. Issue 1 (December 2018) - Hindley, J.; Graham, B.; Pulgarin-R., P.; Burg, T.
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.